2022
DOI: 10.37190/ppmp/156609
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I) recovery on thiomorpholine - modified functional polymer

Abstract: The functional polymer containing heterocyclic ligands was synthesized by microwave modification of a crosslinked poly(vinylbenzyl chloride–divinylbenzene) matrix with thiomorpholine. The modification yield was 89.3%. The sorbent was used to recover Ag(I) from the synthetic and real chloride solutions. The maximum sorption capacity of Ag(I) was approximately 180 mg Ag/g. The sorption kinetic data were well-fitted to the pseudo-first-order kinetic model. The degree of silver desorption was approximately 50.0% u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…For Resin I, this value was lower than the qmax calculated from the linear regression. The maximum sorption capacity of AgCl4 3-obtained by the Dubinin-Radushkevich isotherm model is 151.3, 120.4, 131.6, and 85.2 [mg Ag(I)/g] for functional polymers containing heterocyclic ligands, i.e., thiomorpholine, 4-tert-butylpyridine, pyrrolidine, and 3-morpholinopropylamine ligands, respectively (Pilśniak-Rabiega and Wolska, 2021;Pilśniak-Rabiega and Wolska, 2022). The OCS-ET-TU adsorbent based on a natural corn stalk modified by grafting epithiochlorohydrine and thiourea could selectively adsorb AgCl4 3-from the Ag(I) single and Ag(I)-Cu(II)-Ni(II) simulate nickel electrolyte system (Li et al, 2018).…”
Section: Sorption Isotherm Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For Resin I, this value was lower than the qmax calculated from the linear regression. The maximum sorption capacity of AgCl4 3-obtained by the Dubinin-Radushkevich isotherm model is 151.3, 120.4, 131.6, and 85.2 [mg Ag(I)/g] for functional polymers containing heterocyclic ligands, i.e., thiomorpholine, 4-tert-butylpyridine, pyrrolidine, and 3-morpholinopropylamine ligands, respectively (Pilśniak-Rabiega and Wolska, 2021;Pilśniak-Rabiega and Wolska, 2022). The OCS-ET-TU adsorbent based on a natural corn stalk modified by grafting epithiochlorohydrine and thiourea could selectively adsorb AgCl4 3-from the Ag(I) single and Ag(I)-Cu(II)-Ni(II) simulate nickel electrolyte system (Li et al, 2018).…”
Section: Sorption Isotherm Studiesmentioning
confidence: 99%
“…The recovery of Ag(I) from chloride solution was studied using sorbents containing heterocyclic functional groups (Pilśniak-Rabiega and Wolska, 2020;Pilśniak-Rabiega and Wolska, 2021;Pilśniak-Rabiega and Wolska, 2022). Kinetic studies indicated that the adsorption reaction follows the pseudofirst-order kinetics.…”
Section: Resin IIImentioning
confidence: 99%
See 3 more Smart Citations